Community service sentencing for corporations: Emily M. Homer and George E. Higgins - Homer, Emily M. (Criminal justice policy review, 2021)
This study examines if judges sentence criminal corporations that are more blameworthy in the commission of crimes to community service penalties. This blameworthiness consideration is drawn from the focal concerns framework. The study uses data compiled by the U.S. Sentencing Commission from court documents for the cases of 1125 corporations that were sentenced in federal criminal courts nationwide between October 1, 2010, and September 30, 2017. Results showed that corporations with higher base fines were significantly more likely to be sentenced to terms of community service compared to those corporations with base fines. Policy implications are discussed.